Hematopoiesis in numbers - Cosgrove, Jason; Hustin, Lucie S.P.; de Boer, Rob J.; Perié, Leïla (Trends in immunology, 2021)
Hematopoiesis is a dynamic process in which stem and progenitor cells give rise to the ~1013 blood and immune cells distributed throughout the human body. We argue that a quantitative description of hematopoiesis can help consolidate existing data, identify knowledge gaps, and generate new hypotheses. Here, we review known numbers in murine and, where possible, human hematopoiesis, and consolidate murine numbers into a set of reference values. We present estimates of cell numbers, division and differentiation rates, cell size, and macromolecular composition for each hematopoietic cell type. We also propose guidelines to improve the reporting of measurements and highlight areas in which quantitative data are lacking. Overall, we show how quantitative approaches can be used to understand key properties of hematopoiesis. Informed by published measurements, our calculations suggest that, in mice, 5 × 103 hematopoietic stem cells (HSCs) can give rise to 1010 hematopoietic cells, while, in humans, 2.5 × 104–1.3 × 106 HSCs can give rise to 1013 mature hematopoietic cellsIn humans and mice, most hematopoietic cells are short-lived, on the order of days or weeks. As such, blood cells are constantly being produced to maintain blood homeostasis. In humans, blood cells account for 90% of all cellular turnover.Our calculations predict that the amount of murine and human myeloid and erythroid cells produced each day are approximately the same order of magnitude, despite the absolute number of erythroid cells being several orders of magnitude higher than myeloid cells in both species. This is due to large differences in the expected lifespan of each cell type.Despite recent progress, reports on the absolute measurements of cell numbers across tissues throughout lifespans are missing for many cell types and species, particularly in humans; this represents a fruitful area of empirical investigation.